Dominant bacterial taxa drive microbiome differences of juvenile Pacific oysters of the same age and variable sizes - English, Mary K.; Langdon, Chris J.; Schubiger, Carla B.; Mueller, Ryan S. (Frontiers in Microbiomes, 2023)
Oyster aquaculture is a growing industry that depends on production of fast-growing, healthy larvae and juveniles (spat) to be sold to farmers. Despite nearly identical genetics and environmental conditions in the early life stages of oysters, larvae and spat sizes can vary drastically. As the microbiome can influence the health and size of marine invertebrates, we analyzed the microbiomes of differently-sized juvenile Pacific oyster (Crassostrea gigas) spat of the same age to examine the relationship of their microbiomes with size variation. We used 16S sequencing of 128 animals (n = 60 large, n = 68 small) to characterize the microbiomes of each size class, comparing alpha diversity, beta diversity, and differentially abundant taxa between size classes. We observed that small spat had higher alpha diversity using measures that considered only richness, but there was no difference in alpha diversity between the two size classes using measures that incorporate compositional metrics. Additionally, large and small spat had distinct microbiomes, the separation of which was driven by more dominant bacterial taxa. Taxa that were differentially abundant in large oysters were also more abundant overall, and many appear to have roles in nutrient absorption and energy acquisition. The results of this study provide insight into how the microbiome of C. gigas may affect the early development of the animal, which can inform hatchery and nursery practices.